cavsiopy: a Python package to calculate and visualize spacecraft instrument orientation - Kalafatoglu Eyiguler, E. Ceren; Holley, Warren; Howarth, Andrew D.; Danskin, Donald W.; Pandey, Kuldeep; Martin, Carley J.; Gillies, Robert G.; Yau, Andrew W.; Hussey, Glenn C. (Frontiers in Astronomy and Space Sciences, 2023)
Spacecraft attitude plays an important role in the observations of various atmospheric, planetary, and terrestrial parameters and phenomena that are of interest to the scientific community. Precise measurements from imagers, particle sensors, and antennas require accurate knowledge of instrument orientation. cavsiopy is an easy-to-install and use, light-weight open-source Python package for researchers who need to consider instrument pointing direction and observation geometry. cavsiopy contains the coordinate transformation routines and the corresponding rotation matrices from the spacecraft orbital reference frame (ORF) to any of the Geocentric Equatorial Inertial for epoch J2000 (GEI J2K) / International Celestial Reference Frame (ICRF), Earth Centred Earth Fixed (ECEF), International Terrestrial Reference Frame (ITRF), geodetic North-East-Down, and geocentric North-East-Center coordinate systems. Additionally, cavsiopy includes routines for importing Swarm-E ephemeris and generic Two-Line-Element (TLE) data files, and for the calculation of spacecraft azimuth, elevation and orbital parameters, as well as the 2D/3D visualization of the geometry between the instrument and the target. Functionality and utilization of cavsiopy for research problems are demonstrated with examples and visualizations for the Radio Receiver Instrument (RRI) and the Fast Auroral Imager (FAI) of e-POP/Swarm-E.